2013
DOI: 10.1007/s00429-013-0512-z
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of fluid intelligence and working memory revealed by lesion mapping

Abstract: Although cognitive neuroscience has made valuable progress in understanding the role of the prefrontal cortex in human intelligence, the functional networks that support adaptive behavior and novel problem solving remain to be well characterized. Here, we studied 158 human brain lesion patients to investigate the cognitive and neural foundations of key competencies for fluid intelligence and working memory. We administered a battery of neuropsychological tests, including the Wechsler Adult Intelligence Scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
58
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 128 publications
(68 citation statements)
references
References 68 publications
9
58
0
1
Order By: Relevance
“…We were able to identify joint sources of anatomical and cognitive variation at multiple levels broadly consistent with previous functional and lesion literature on the distributed nature of high-level cognitive abilities including with areas of the core “rich club,” fronto-parietal network, and the white matter tracts that form the anatomical basis for functional communications within this network (Engle et al, 1999a; Barbey et al, 2014). …”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…We were able to identify joint sources of anatomical and cognitive variation at multiple levels broadly consistent with previous functional and lesion literature on the distributed nature of high-level cognitive abilities including with areas of the core “rich club,” fronto-parietal network, and the white matter tracts that form the anatomical basis for functional communications within this network (Engle et al, 1999a; Barbey et al, 2014). …”
Section: Discussionsupporting
confidence: 77%
“…This residual factor, produced by a data-driven approach, provides converging evidence for the importance of these regions to cognitive function (Barbey et al, 2014; Colom et al, 2009; Luders et al, 2009; McDaniel, 2005), and unlike the first-level components it cannot be interpreted as an artifact of demographic variations or gross morphology because these sources of variance were removed in the first-level analysis. Thus, we suggest that the novel, data-driven first-level sources of variation may serve as useful controls in exploring high-level hypotheses for links between anatomical variations to cognitive function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The failure to detect statistically significant changes at the hypothesized brain regions (mainly in frontal and parietal cortices) may account for the lack of results in this regard. Indeed, the large-scale lesion study reported by Barbey et al (2014) might be consistent with this view. Analyzing the overlap between fluid intelligence (Gf) and four working memory distinguishable cognitive factors (verbal/numeric working memory, spatial working memory, working memory manipulation, and working memory monitoring) meager overlap was found for Gf and monitoring processes (as assessed by 1-back, 2-back, and 3-back tasks): the overlap was circumscribed to a small region within the right inferior parietal cortex.…”
Section: Discussionsupporting
confidence: 66%
“…With the advent of fMRI imaging, neural substrates of general and fluid intelligence have been mapped in the brain, primarily to frontoparietal and temporal locations (Barbey, Colom, Paul, & Grafman, 2014; Hampshire, Thompson, Duncan, & Owen, 2011; Preusse, van der Meer, Deshpande, Krueger, & Wartenburger, 2011; Colom, Karama, Jung, & Haier, 2010; Woolgar et al, 2010). Furthermore, rigorous attempts at identifying general and specific components of intelligence by combining neuroimaging and use of latent variable modeling have been undertaken recently (Hampshire, Highfield, Parkin, & Owen, 2012).…”
Section: Introductionmentioning
confidence: 99%